A clinical study on relationship between visualization of cardiac fibroblast activation protein activity by Al18F-NOTA-FAPI-04 positron emission tomography and cardiovascular disease - Lyu, Zhehao; Han, Wei; Zhao, Hongyue; Jiao, Yuying; Xu, Peng; Wang, Yangyang; Shen, Qiuyi; Yang, Shuai; Zhao, Changjiu; Tian, Lin; Fu, Peng (Frontiers in Cardiovascular Medicine, 2022)
Objective FAP plays a vital role in myocardial injury and fibrosis. Although initially used to study imaging of primary and metastatic tumors, the use of FAPI tracers has recently been studied in cardiac remodeling after myocardial infarction. The study aimed to investigate the application of FAPI PET/CT imaging in human myocardial fibrosis and its relationship with clinical factors. Materials and methods Retrospective analysis of FAPI PET/CT scans of twenty-one oncological patients from 05/2021 to 03/2022 with visual uptake of FAPI in the myocardium were applying the American Heart Association 17-segment model of the left ventricle. The patients’ general data, echocardiography, and laboratory examination results were collected, and the correlation between PET imaging data and the above data was analyzed. Linear regression models, Kendall’s TaU-B test, the Spearman test, and the Mann–Whitney U test were used for the statistical analysis. Results 21 patients (60.1 ± 9.4 years; 17 men) were evaluated with an overall mean LVEF of 59.3 ± 5.4%. The calcific plaque burden of LAD, LCX, and RCA are 14 (66.7%), 12 (57.1%), and 9 (42.9%). High left ventricular SUVmax correlated with BMI (P < 0.05) and blood glucose level (P < 0.05), and TBR correlated with age (P < 0.05). A strong correlation was demonstrated between SUVmean and CTnImax (r = 0.711, P < 0.01). Negative correlation of SUVmean and LVEF (r = −0.61, P < 0.01), SUVmax and LVEF (r = −0.65, P < 0.01) were found. ROC curve for predicting calcified plaques by myocardial FAPI uptake (SUVmean) in LAD, LCX, and RCA territory showed AUCs were 0.786, 0.759, and 0.769. Conclusion FAPI PET/CT scans might be used as a new potential method to evaluate cardiac fibrosis to help patients’ management further. FAPI PET imaging can reflect the process of myocardial fibrosis. High FAPI uptakes correlate with cardiovascular risk factors and the distribution of coronary plaques.